2010
DOI: 10.1177/0305735610376261
|View full text |Cite
|
Sign up to set email alerts
|

The impact of background music on adult listeners: A meta-analysis

Abstract: Background music has been found to have beneficial, detrimental, or no effect on a variety of behavioral and psychological outcome measures. This article reports a meta-analysis that attempts to summarize the impact of background music. A global analysis shows a null effect, but a detailed examination of the studies that allow the calculation of effects sizes reveals that this null effect is most probably due to averaging out specific effects. In our analysis, the probability of detecting such specific effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
192
4
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(214 citation statements)
references
References 102 publications
14
192
4
4
Order By: Relevance
“…Technical problems that hindered comprehension were poor sound quality, fluctuations in volume, interference and background music. This finding supports previous research in multimedia learning theory and elsewhere, which indicates that extraneous sound or music hinders task completion and information retention (Kämpfe, et al, 2010;Moreno & Mayer, 2000a), particularly when music is faster and louder (Thompson et al, 2012). Although Thompson et al (2012) cite evidence that softer music has the potential to aid concentration, the present data indicate that music elicits a largely negative reaction, and should thus be avoided in the interests of creating resources appropriate for the largest range of viewers.…”
Section: Comprehensionsupporting
confidence: 88%
“…Technical problems that hindered comprehension were poor sound quality, fluctuations in volume, interference and background music. This finding supports previous research in multimedia learning theory and elsewhere, which indicates that extraneous sound or music hinders task completion and information retention (Kämpfe, et al, 2010;Moreno & Mayer, 2000a), particularly when music is faster and louder (Thompson et al, 2012). Although Thompson et al (2012) cite evidence that softer music has the potential to aid concentration, the present data indicate that music elicits a largely negative reaction, and should thus be avoided in the interests of creating resources appropriate for the largest range of viewers.…”
Section: Comprehensionsupporting
confidence: 88%
“…His research suggested that slower music is related to a slower pace of peoples' movement in a retail environment, and, as a result, more time and money spent there; while fast musical tempo reproduced in a restaurant caused a shorter duration of eating time [6]. Focusing more on the effect of music tempo, Kampfe, Sedlmeier, and Renkewitz [7] asserted that hearing background music characterized by a fast tempo leads to an increase in the pace of certain behaviours, such as drawing, reading, walking and running, and eating and drinking. In general, there are two fundamental hypotheses for these effects; the first is the synchronization of the movements to the musical beat, while the second is the increase in the arousal found with fast-tempo music [8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not find that background music had an effect on verbal learning (Jäncke & Sandmann, 2010). Based on a meta-analysis, similar results were achieved by Kämpfe, Sedlmeier & Renkewitz (2011) who, however, looked at many areas of human activity (commerce, sports, transportation, etc.) and point out discrepancies in the research methodology of individual studies that can distort results and lead to erroneous conclusions.…”
Section: Types Of Musical Activities Used For Learningmentioning
confidence: 61%